1988
DOI: 10.1111/j.1445-2197.1988.tb01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Breast Cancer: Cosmetic and Functional Results After Treatment by Conservative Techniques

Abstract: patients with early breast cancer were referred to the Department of Radiation Oncology at Westmead Hospital for radiation therapy following initial tumour excision. After a median follow-up of 26 months, five patients developed a loco-regional recurrence (4%) and nine developed metastatic disease but with local control.There were 105 eligible patients who were sent a letter/questionnaire which included: a request to attend a clinic, to allow an objective assessment of the cosmetic result of the treated breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…It may present as heaviness or aching of the arm, swelling of fingers, or sometimes as difficulty putting on long sleeves. The risk of severe lymphedema is approximately 6% after single treatment, but goes up to 30% after the combination of surgery (axillary clearance) and radiotherapy treatment [80]. Lymphedema may occur at any time after treatment (even 20-30 years after axillary treatment).…”
Section: Presumablymentioning
confidence: 97%
“…It may present as heaviness or aching of the arm, swelling of fingers, or sometimes as difficulty putting on long sleeves. The risk of severe lymphedema is approximately 6% after single treatment, but goes up to 30% after the combination of surgery (axillary clearance) and radiotherapy treatment [80]. Lymphedema may occur at any time after treatment (even 20-30 years after axillary treatment).…”
Section: Presumablymentioning
confidence: 97%
“…20 It is also noteworthy that there is a lack of concordance between different observer groups. [22][23][24] Sneeuw et al reported that patients demonstrated significantly greater variation ( Ͻ 0.10) in aesthetic scoring compared with professionals ( ϭ 0.64) using four-point subscales. 20 In contrast, a study by Cohen et al, which used a global fivepoint scale, reported greater internal consistency among patients (Cronbach ␣ ϭ 0.92) compared with medical professionals (Cronbach ␣ ϭ 0.74 to 0.89).…”
Section: Subjective Ratingsmentioning
confidence: 97%
“…This procedure involves removal of excess breast tissue to reshape and lift the breasts. Benefits of the surgery include increased comfort in your upper back, neck and shoulders; less shoulder pressure from bra straps; increased ability to exercise and participate in physical activities; and a more positive self-image 20 . The surgery may also help you breathe and sleep easier.…”
Section: Gynaecomastiamentioning
confidence: 99%
“…Follicular micro or mini grafts are used to provide the desired density of hair. Since the new transplanted hair is from one's own body, it will grow naturally with time & one can shampoo, trim or even shave it 5 .…”
Section: Types Of Cosmetic Surgeriesmentioning
confidence: 99%
See 1 more Smart Citation